Homoepitaxial diamond film growth: High purity, high crystalline quality, isotopic enrichment, and single color center formation (Phys. Status Solidi A 11∕2015). Issue 11 (November 2015) - Teraji, Tokuyuki; Yamamoto, Takashi; Watanabe, Kenji; Koide, Yasuo; Isoya, Junichi; Onoda, Shinobu; Ohshima, Takeshi; Rogers, Lachlan J.; Jelezko, Fedor; Neumann, Philipp; Wrachtrup, Jörg; Koizumi, Satoshi
Abstract : With next‐generation optical/electronic devices in mind, the growth of homoepitaxial diamond films that possess higher crystalline quality, higher chemical purity, and higher carbon isotopic ratio is indispensable. In order to improve both the purity and crystalline quality of homoepitaxial diamond films, an advanced growth condition, higher oxygen concentration in the growth ambient, was applied (see the Feature Article by Tokuyuki Teraji et al., pp.2365–2384 ). Under the proposed growth conditions, a thick diamond film of ≥30 μm was reproducibly deposited with keeping high purity and substantially flat surface. The cover figure shows the evolution of the surface morphology of such sample. The film thickness T f of the homoepitaxial diamond in each image is 0 (substrate), 3, 30, and 120 μm, respectively. Morphological patterns move to the crystallographic off direction of the substrate with increasing film thickness. The background of the cover shows confocal microscope images taken by scanning in either x ‐ z (depth) or x ‐ y (in‐plane) directions. These images indicate that the nitrogen concentration in homoepitaxial diamond film is extremely low. The advanced growth techniques will open up a new field of diamond research that requires extremely low impurity concentration, such as power devices and quantum information devices.